Biological nitrification inhibition by Brachiaria grasses mitigates soil nitrous oxide emissions from bovine urine patches - Byrnes, Ryan C.; Nùñez, Jonathan; Arenas Calle, Laura N.; Rao, Idupulapati M.; Trujillo, Catalina; Álvarez, Carolina; Arango, Jacobo; Rasche, Frank; Chirinda, Ngonidzashe (Elsevier, 2017)
High nitrogen (N) concentration in bovine urine, which generally exceeds plant N uptake rates, results in the formation of hotspots of N loss when bovine urine is deposited on grazed pasture soils. High spatial variability in the distribution of urine patches in grazed pastures poses a major challenge to mitigate N losses. Some exudates from the roots of several tropical forage grasses were shown to inhibit the activity of soil nitrifiers; a process known as biological nitrification inhibition (BNI).We hypothesized that nitrate (NO3) production and nitrous oxide (N2O) emissions from urine patches deposited on soils under forage grasses with high BNI capacity are lower than those with forage grasses with low BNI capacity. This hypothesis was tested using field plots of two tropical forage grass cultivars, Brachiaria humidicola cv. Tully (BT) and interspecific Brachiaria hybrid cv. Mulato (BM) which, correspondingly, have high and low BNI capacity. Nitrification rates and amoA gene copy numbers of ammonia oxidizing archaea (AOA) and bacteria (AOB) in soils under the two forage grasses were quantified before and after urine and water (control) application, as well, an additional experiment was conducted to quantify denitrification potential. Moreover, soil N2O emissions from simulated urine (0.123 kg N m_2) and water patches were monitored over a 29-day period. Results showed a greater suppression of nitrification, denitrification and AOA abundance in soils under BT than those under BM. Positive relationships (p < 0.05) existed between AOA and AOB abundance and NO3 _ contents in soils under BM. Bovine urine resulted in higher cumulative N2O fluxes from soils under BM (80 mg N2O-N m_2) compared to those under BT (32 mg N2O-N m_2). Consequently, N2O emission factors were higher for soils under BM (0.07%) than under BT (0.00002%). We conclude that tropical forage grasses with high BNI capacity play a key role in mitigating N2O emissions from bovine urine patches in archaea-dominated soils. This suggests that wide-spread adoption of tropical forage grasses with high BNI capacity may have a great potential to tighten N cycling in grazed pastures.